Study guides

☆☆

Q: What is the factorization of the trinomial below -2x3-2x2 12x?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

If you mean: x2-12x+35 then it is (x-7)(x-5) when factored

If you mean: 4x squared+12x-40 then it is (x+5)(x-2) after dividing all terms by 4

GCF = 12x.24x = 2(12x)36x3 = 3x2(12x)

Terms in polynomials are simply separated by a plus or minus sign. For example, if you had: x+12x, that would be a binomial (two terms). A trinomial is when the expression has three or more terms, 7x+12x-6x.

12x2+13x-35 = (4x-5)(3x+7) 12x2 + 13x- 35 let's find two factors of -420 (12*-35) whose sum is 13, which are 28 and -15 (12x + 28)(12x - 15) now simplify by 4 and 3 (3x + 7)(4x - 5)

Related questions

-2x(x + 3)(x + 2)

x2+12x+28Improved Answer:--x2+12x+28 = (-x+14)(x+2) when factored

I assume your problem is: -2x3-2x2+12x-2x(x2-x-6)-2x(x-3)(x+2)

-2x3 + 2x2 + 12x =(-2x) (x2 - x - 6) =(-2x) (x+2) (x-3)

If you mean: x2-12x+35 then it is (x-7)(x-5) when factored

What value, in place of the question mark, makes the polynomial below a perfect square trinomial?x2 + 12x+ ?

x3 - 12x2 + 35x = x(x2 - 12x + 35) = x(x - 5)(x - 7)

If you mean x^2 -12x+35 then it is a quadratic expression which can be factored in the form of (x-7)(x-5)

I would do this. Multiply through by -1 -1 ( -X^2 +12X +28 ) = X^2 -12X -28 (X+2)(X-14)

(-2x3 - 2x2 + 12x) = -2x (x2 + x - 6) = -2x (x + 3) (x - 2)

(x + 8)(x + 4)

-2x3 + 2x2 + 12x = -2x(x2 - x - 6) = -2x(x2 + 2x - 3x - 6) = -2x[ x(x + 2) - 3(x + 2) ] = -2x(x - 3)(x + 2)

People also asked